2004
DOI: 10.1002/jmri.20015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance parallel imaging at 3.0 Tesla: Technical feasibility and advantages

Abstract: Purpose: To quantify changes in signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), specific absorption rate (SAR), RF power deposition, and imaging time in cardiac magnetic resonance imaging with and without the application of parallel imaging at 1.5 T and 3.0 T. Materials and Methods:Phantom and volunteer data were acquired at 1.5 T and 3.0 T with and without parallel imaging.Results: Doubling field strength increased phantom SNR by a factor of 1.83. In volunteer data, SNR and CNR values increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…This was because of the dense and extensive sampling of the central region of the k-space to overcome undersampling even if parallel imaging was used, i.e., overcoming motion artifact, as reported in a previous work (20). The deteriorated results for L/C(1) compared with those for L/C(2) indicated that for the same values of matrix size, blade width, and number of blades, the advantage of shorter ETL could not overcome the effect of k-space undersampling (21). The streak artifact arises in the process of gridding acquired data to the parallel k-space from the oblique trajectory, and the undersampling of kspace was shown to increase the artifact (13,20).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This was because of the dense and extensive sampling of the central region of the k-space to overcome undersampling even if parallel imaging was used, i.e., overcoming motion artifact, as reported in a previous work (20). The deteriorated results for L/C(1) compared with those for L/C(2) indicated that for the same values of matrix size, blade width, and number of blades, the advantage of shorter ETL could not overcome the effect of k-space undersampling (21). The streak artifact arises in the process of gridding acquired data to the parallel k-space from the oblique trajectory, and the undersampling of kspace was shown to increase the artifact (13,20).…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, increasing blade coverage was expected to improve not only motion correction effects but also the signal-to-noise ratio (SNR), as a result of oversampling, as was shown in the L/C(3) compared with other scan conditions. Although reduced ETL was expected to decrease image blurring and improve the overall image quality, the L/C(1) image gave the worst score because of an increase in image artifacts due to k-space undersampling, which was found to be unrecoverable with iPAT (21).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential difficulties, it is now clear that high field strength is beneficial for many applications such as brain [10][11][12], heart [4,13,14], or musculoskeletal imaging [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical shift and susceptibility artifacts also increase linearly with B 0 , resulting in difficulties in analyzing water-fat transitions and in signal losses in regions of susceptibility differences. Increasing the sampling bandwidth can reduce chemical shift artifacts, but at the expense of SNR [1,2,4]. The applied RF has to be adapted to higher Larmor frequencies, making its penetration into tissues more difficult [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…McGee et al (9) showed increasing the field strength from 1.5-T to 3-T resulted in a 1.83 increase in signal-tonoise ratio in five volunteers. They also tested parallel imaging at 3-T.…”
Section: Technical Advancesmentioning
confidence: 98%